Effects of human impact on the beds of minor watercourses of the Aegean Island of Icaria (Greece) - Tsermegas, Irena (Quaestiones Geographicae, 2012)
The aim of the work was to show the scale of changes of riverbeds in the conditions of Mediterranean climate and many ages of human impact, on the example of Icaria, an island situated in the eastern part of the Aegean Sea. The most altered riverbed fragments were selected and the main types of conversion were defined based on the terrain mapping and the interviews with the inhabitants. They are as follows: the increase in the seasonality of tides, the transformation of the riverbed fragments into paths, the narrowing of the riverbeds, the strengthening of their bottoms and banks, the partitioning of the riverbeds with the proprietary boundaries, the inclusion of the riverbeds into the irrigation system and the creation of infrastructure to be used by watermills. The riverbeds that were altered the most were the ones within villages, up to 400 m above sea level. Changes described were taking place in stages. In antiquity they concerned only the estuary parts. Until the 1950s they covered arable areas inside the island. After 1970 there followed a drastic diminishing of flows in the riverbeds and there appeared riverbeds with artificial bottoms.